IMPLEMENTASI PEMBELAJARAN SOSIAL EMOSIONAL PADA KEGIATAN PEMBELAJARAN TEKS TANGGAPAN MELALUI PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) - Ilmia Turrofiah; Martutik Martutik; Ilmia Turrofiah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: This research aims to describe the implementation of planning and implementation of social emotional learning in response text using the CRT approach. The method in this research in qualitative using Miles and Huberman’s data analysis theory. The result of this research include 1) Social emotional learning planning activities applied based on CASEL theory in teaching modules, namely self-awareness, self-management, social awareness, relationship skills and responsible decision-making. 2) In learning activities, social emotional learning is implemented, namely self-awareness, self-management, social awareness, relationship skills and responsible decision-making